Pollen morphology of Teucrium L. (Lamiaceae, Ajugoideae) in Libya (Bangladesh Journal of Plant Taxonomy, 2017)
Pollen grains of 11 taxa of Teucrium from Libya were examined using lightmicroscopy (LM) and scanning electron microscopy (SEM) in order to provide better insight on the evaluation of palynological attributes for species characterization of Teucrium with special emphasis on the five Libyan endemic. Two main pollen shapes were documented; subprolate and prolate or perprolate in T. fruticans. The exine sculpture inspected at surface, operculum and pole were mostly verrucate, perforate or scabrate. Teucrium fruticans attained the phenomenon of pollen dimorphism with two distinct shapes and specifics sculpture for each form. The results validated thetaxonomic significance of pollen grains for the discrimination among Teucrium species in Libya.Bangladesh J. Plant Taxon. 24(2): 219–226.